Pengaruh Persepsi Kemudahan, Kepercayaan, Lingkungan Sosial, dan Motivasi Hedonis terhadap Minat Penggunaan E-Money di Daerah Istimewa Yogyakarta - Deden Iwan Kusuma; Suratriningsih Susilowati (Syntax Corporation Indonesia, 2024)
The purpose of this research is to ascertain how the influence of perceptions of convenience, trust, social environment and hedonic motivation on the intention to use e-money in the Special Region of Yogyakarta. This study uses primary data collection in the form of questionnaires which are distributed via WhatsApp and Instagram media. The data analysis tool for this research is to use multiple regression analysis, which is to find out how much influence perceptions of convenience, trust, social environment, and hedonic motivation have on the interest in using e-money in the Special Region of Yogyakarta. These results indicate that perceived convenience and trust have a negative effect on the intention to use e-money in the Special Region of Yogyakarta, while the social environment and hedonic motivation have a positive effect on the intention to use e-money in the Special Region of Yogyakarta.